Liver-specific RORα deletion does not affect the metabolic susceptibility to western style diet feeding - Antonio Molinaro; Robert Caesar; Laurent L'homme; Ara Koh; Marcus Ståhlman; Bart Staels; Fredrik Bäckhed (Elsevier, 2019)
Objectives: The nuclear receptor superfamily is a potential target for the development of new treatments for obesity and metabolic diseases. Increasing evidence has pointed towards the retinoic acid-related orphan receptor-alpha (RORα) as an important nuclear receptor involved in several biological processes. RORα full body knockout mice display improved metabolic phenotypes on both chow and high fat (60% fat, 20% carbohydrate) diets, but also have severe behavioral abnormalities. Here we investigated the effect of hepatic RORα by generating mice with liver-specific RORα deletion to elucidate the role of this nuclear receptor on host metabolism. Methods: 8 week-old mice with liver-specific RORα deletion and littermate controls were fed either chow or western-style diets (40% fat, 40% carbohydrate) for 12 weeks. Metabolic phenotyping was performed at the end of the dietary intervention. Results: Here, we show that hepatic RORα deletion does not affect the metabolic susceptibility to either chow or western-style diet in terms of glucose metabolism and adiposity. Conclusions: Our data indicate that liver deletion of RORα does not have a pivotal role in the regulation of hepatic glucose and lipid metabolism on chow or western-style diet. Keywords: RORα, Obesity, Glucose metabolism, Steatosis